Bruno da Longobucco (da Longoburgo): The first academic surgeon in the Middle Ages - Pata, Francesco; Linardi, Cataldo; Brady, Richard R.; Pellino, Gianluca; D’Ambrosio, Giancarlo; , the Bruno da Longobucco study group; Vennari, Marialuisa; Murrone, Domenico (Frontiers in Surgery, 2022)
Bruno da Longobucco (1200-1286 BC) was born at the turn of the 13th Century Longobucco (Calabria, Italy), at that time named Longoburgo. He was the first academic surgeon of the Middle Ages, a period when surgery was disregarded by mainstream physicians and was the practice of barbers, charlatans and phlebotomists. After training at the medical school of Salerno and the University of Boulogne, he was one of the founders of the University of Padua and became the first Professor of Surgery. His books Chirurgia Magna and Chirurgia Parva, were ones of the most disseminated surgical texts of the Middle Ages and it is argued helped surgery regain its reputation. Despite his importance to late medieval period, he has been essentially overlooked in the records of the history of surgery. Currently, there are no articles in English about his life indexed on PubMed, Scopus or Embase. One solitary article on Bruno’s life and influence was published in 1960s in a small journal in Italian, but this is no longer active and there is no electronic means to access the original article. The aim of this article is to provide education and rediscovery of the impact of this critical figure, his works and his historic role to the development and renaissance of surgery for contemporary surgeons.